Spatiotemporally Controlled Myosin Relocalization and Internal Pressure Generate Sibling Cell Size Asymmetry - Tri Thanh Pham; Arnaud Monnard; Jonne Helenius; Erik Lund; Nicole Lee; Daniel J. Müller; Clemens Cabernard (iScience, 2019)
Summary: Metazoan cells can generate unequal-sized sibling cells during cell division. This form of asymmetric cell division depends on spindle geometry and Myosin distribution, but the underlying mechanics are unclear. Here, we use atomic force microscopy and live cell imaging to elucidate the biophysical forces involved in the establishment of physical asymmetry in Drosophila neural stem cells. We show that initial apical cortical expansion is driven by hydrostatic pressure, peaking shortly after anaphase onset, and enabled by a relief of actomyosin contractile tension on the apical cell cortex. An increase in contractile tension at the cleavage furrow combined with the relocalization of basally located Myosin initiates basal and sustains apical extension. We propose that spatiotemporally controlled actomyosin contractile tension and hydrostatic pressure enable biased cortical expansion to generate sibling cell size asymmetry. However, dynamic cleavage furrow repositioning can compensate for the lack of biased expansion to establish physical asymmetry. : Biomechanics; Biophysics; Cell Biology; Methodology in Biological Sciences Subject Areas: Biomechanics, Biophysics, Cell Biology, Methodology in Biological Sciences